Slab-beam Interaction in One-way Floor Systems (Journal of Engineering, 2018)
This study focuses on the slab-beam interaction in one-way systems. In the context of this study, slab-beam interaction means how beam deflection can affect moment distribution in one-way slabs. This interaction is usually neglected in the traditional approximate analysis that is adopted in engineering practice and design codes. Slab positive moments have been considered as indicators on the accuracy of approximate methods, as they overestimate negative moments while underestimating positive moments.After proposing of effecting parameters in slab-beam interaction including of panel length and width, beam dimensions, and slab thickness, Buckingham’s  theorem has been adopted to transform the dimensional-model into a non-dimensional qualitative one. Different case studies with finite element models have been adopted to generate points on the proposed qualitative non-dimensional model. Finally, linear regression analyses have been adopted to develop the corresponding quantitative models.Case studies and corresponding regression analysis indicate that non-dimensional parameters adopted in the model are related linearly with a correlation coefficient in the range of 0.97 and that an error up to 250% may be noted due to neglecting the slab-beam interaction. Therefore, a condition related to the relative stiffness of supporting beams should be added to the current conditions for the approximated methods to be more accurate and more compatible with those adopted in the analysis of two-way systems.